Sistem Kontrol Air dan Pencahayaan pada Akuarium Berbasis Internet of Things (IoT) - Hidayat, Dody; Ramli, Ramli (Building of Informatics, Technology and Science (BITS), 2024)
Decorative fish are popular pets that are often kept in pools or aquariums. Aquariums are an effective choice for decorative fish lovers because they make it easy to monitor fish development and settlement arrangements. Important aspects in keeping ornamental fish include feeding, water clarity, and lighting systems. Continuously lit light can cause the growth of molluscs in the aquarium, which reduces the clarity of the water and affects its quality. The occupation of the owners often makes them forget to control the water condition and lighting. Water that is not regularly replaced can cause pH instability, which has a negative impact on fish health. Remaining feed that sits at the bottom of the aquarium and is not filtered by the filter also reduces the clarity of the water. Therefore, it is important to control the water clarity and lighting periodically so that the fish can grow well. The solution for owners who don't have time for water replacement and lighting control is to use an Internet of Things (IoT) based system. IoT allows remote control and monitoring over the Internet. The research developed an IoT system to control water and aquarium lighting using the NodeMCU ESP8266 module connected to the Blynk Cloud. The system is equipped with an ultrasonic sensor to measure water height, a solenoid valve to regulate water flow, LEDs as lighting, and a buzzer as warning, all of which can be controlled via a smartphone.